Chromosome-scale genome assembly of Codonopsis pilosula and comparative genomic analyses shed light on its genome evolution - Chen, Bao-Zheng; Yang, Zi-Jiang; Yang, Ling; Zhu, Yi-Fan; Li, Xu-Zhen; Wang, Lei; Zhou, Ye-Peng; Zhang, Guang-Hui; Li, Da-Wei; Dong, Yang; Duan, Sheng-Chang (Frontiers in Plant Science, 2024)
Introduction Codonopsis pilosula is a significant plant in traditional Chinese medicine, valued for its edible and medicinal properties. However, the lack of available genomic resources has hindered further research. Methods This study presents the first chromosome-scale genome assembly of C. pilosula using PacBio CLR reads and Hi-C scaffolding technology. Additionally, Ks analysis and syntenic depth analysis were performed to elucidate its evolutionary history. Results The final assembly yielded a high-quality genome of 679.20 Mb, which was anchored to 8 pseudo-chromosomes with an anchoring rate of 96.5% and a scaffold N50 of 80.50 Mb. The genome assembly showed a high completeness of 97.6% based on Benchmarking with Universal Single-Copy Orthologs (BUSCO) analysis. Repetitive elements constituted approximately 76.8% of the genome, with long terminal repeat retrotransposons (LTRs) accounting for about 39.17%. Ks and syntenic depth analyses revealed that the polyploidization history of three platycodonoid clade species involved only the γ-WGT event. Karyotype evolutionary analysis identified an ancestral karyotype with 9 protochromosomes for the three platycodonoid clade species. Moreover, non-WGD genes, particularly those arising from tandem duplications, were found to contribute significantly to gene family expansion. Discussion These findings provide essential insights into the genetic diversity and evolutionary biology of C. pilosula, aiding its conservation and sustainable use.